Bilateral renal abscess fusing with the psoas on the right: A case report - Ramzi Mejri (Elsevier, 2022)
Renal abscess is a medical and surgical urological emergency whose diagnosis has been improved by modern imaging.It often poses a problem of therapeutic management between antibiotic therapy or the association of a drainage. Most abscesses are unilateral, the bilateral nature of the abscessed lesions suggests a hematogenous diffusion.We report a case of a bilateral renal abscess fusing to the psoas muscle on the right that progressed well with antibiotic treatment and percutaneous drainage.